Türkiye'de yenilenebilir enerji ekonomisi ve Ankara iline ait SWOT analizi - Mutlu, Ediz (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / İktisat Anabilim Dalı / Yönetim Ekonomisi Bilim Dalı, 2013)
Geçmişten günümüze gelişen teknoloji ve nüfus artışı, enerjiye olan talebi arttırmıştır. Gelecekte ise bu artışın devam edeceği öngörülmektedir. Artan enerji talebini karşılamak için enerji piyasasına yeni etmenler (yenilenebilir enerji kaynakları) eklenmektedir. Ülkeler rekabet gücünü artırmak üzere ekonomiyi büyütecek ve yaşam standartlarını yükseltecek yeterli, sürekli ve temiz enerjiye ihtiyaç duymaktadırlar. Bu çerçevede Türkiye?deki enerji durumuna genel olarak bakıldığında; Türkiye?nin enerji tüketimi ve ithalatı, hızlı bir artış içerisindedir. Ülkemizin enerjide dışa bağımlılığının azaltılması için yenilenebilir enerji kaynaklarının kullanımını artırmamız ve arz güvenliği için enerjide çeşitlilik yaratmamız gerekmektedir. Bu tezin amacı, yenilenebilir enerji kaynakları hakkında genel bir bilgi vererek, Türkiye?deki durumunu değerlendirmek, bu sektördeki ekonomiyi analiz etmek ve Ankara ilindeki yenilenebilir enerji olanaklarından bahsedilerek örnek bir SWOT analizi yapmaktır. Çalışmanın birinci bölümünde; Dünyada ve Türkiye?deki genel enerji piyasası ve politikalarından bahsedilmiş ve ayrıca güvenli bir transit ülke olarak Türkiye?nin rolü üzerinde durulmuştur. Bunun yanı sıra, enerji bağlamında Türkiye ? AB ilişkilerine de yer verilmiştir. İkinci bölümde; yenilenebilir enerjinin genel tanımı ve yenilenebilir enerji kaynakları üzerinde durulmuştur. Bu kaynaklardan her birinin Türkiye?deki potansiyeline değinilmiştir. Üçüncü bölümde; Türkiye?deki yenilenebilir enerji ekonomisinden bahsedilmiş ve son olarak da Ankara ilindeki yenilenebilir enerji olanakları üzerinde durularak örnek bir SWOT analizi yapılmıştır.

From past to nowadays, Energy demand has been increasing by the reason of technological developments and population growth. In the future such an increasing trend is predicted to endure. In order to meet the increasing energy demand, new factors (renewable energy sources) are incorporated in the energy market. In order to increase their competitive strength, countries need continual and clean energy, which is going to grow the economy and their living standard. In this context, when we look at Turkey's aspect, energy consumption and import increase quickly. In order to decrease our country's energy dependence on foreign countries, we should increase the usage of renewable energy sources and for the security of supplies, we should create variability in energy. The aim of this study is to examine the renewable energy sources in Turkey while giving general information about it, to analyze the economy in this sector and to give an example of a SWOT analysis that is made in Ankara. In the first chapter of this study; it was mentioned about the energy market and policies on the world and in Turkey and also, Turkey's role as a safe transit route was emphasized. Add to this, Turkey - European Union (EU) relations were examined in respect of energy. In the second chapter; general description of renewable energy and its sources was examined. This chapter also deals with each of these sources and their potentials in Turkey. In the last chapter, renewable energy economy in Turkey was mentioned and lastly the renewable energy opportunities in Ankara city were examined and also example SWOT analysis was given in Ankara.

This study deals with the impact of French poet Guillaume Apollinaire on Turkish poet Cemal Süreya. The aim of this study is to reveal similar points on both poets and realise the impact of Apollinaire?s poems on Süreya?s literary works. In this study, common points have been emphasized considering the description of lives and sense of art of both poets. Firstly, Süreya?s Apollinaire translations and afterwards different poets? translations of Apollinaire poems have been compared and finally similarities and differences examined. But in this study, principally, Süreya?s poems which seem to be similar to Apollinaire?s ones have been examined. As a conclusion, detailed explorations and evaluations, it has been deduces that there is no substantial impact of Apollinaire?s poems observed on Süreya?s poems. Common and similar points on both poet?s poems did not retain Süreya to produce his own unique poems. Cemal Süreya has a genuine poems which differred from Guillaume Apollinaire poems in terms of many particullar points.
Renewable energy economy in Turkey and SWOT analysis of Ankara city
Keywords: Ekonomi; Enerji; Economics; Energy